The policy framework and strategies for sustainable industrial development in Kerala: An exploration - P Noufal and KV Ramachandran (International Journal of Applied Research, 2017)
Kerala is making rapid strides on its manufacturing front and the micro, small, and medium industrial enterprises operating in the State have acquired global competence in quality and in the ability to deliver its best. The Industrial and Commercial Policy of the Government attempts to transform the State into a vibrant entrepreneurial society with innovative strategies and practices needed for its inclusive, environment-friendly, and sustainable economic growth. The Government has Successfully implemented various schemes for better improving the industrial environment of the State through the development of exemplary industrial infrastructure, promoting innovations and entrepreneurship, and providing basic skill development mechanisms. The State has to take adequate steps for nurturing entrepreneurial skills, helps in the acquisition of new capacities, and promotes research and development attuned to the industrial needs of the economy so as to raise its productivity. It is in the context, the paper attempts to evaluate the industrial and commercial policy of the State i terms of its vision, objectives, strategy, and some innovative mechanisms